2016
DOI: 10.3389/fphys.2016.00301
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic and Circadian Systems: Driving Mammary Gland Development and Function

Abstract: Since lactation is one of the most metabolically demanding states in adult female mammals, beautifully complex regulatory mechanisms are in place to time lactation to begin after birth and cease when the neonate is weaned. Lactation is regulated by numerous different homeorhetic factors, all of them tightly coordinated with the demands of milk production. Emerging evidence support that among these factors are the serotonergic and circadian clock systems. Here we review the serotoninergic and circadian clock sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…However, the amplitude of annual changes in fat and protein levels in our study was greater than what had been observed in bovine milk at much higher latitude. Taking into account all the aforementioned information, we hypothesized that seasonal changes in the chemical composition of camel milk may reflect an endogenous circannual biological rhythm with a strong underlying pacemaker that is generated by the circadian system and entrained by environmental cues (Casey and Plaut, 2012;Suárez-Trujillo and Casey, 2016). To support this hypothesis, El Allali et al (2013) recently demonstrated the existence of an endogenous circadian clock in dromedaries by describing rhythmic daily changes in body temperature under a constant photoperiod and ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the amplitude of annual changes in fat and protein levels in our study was greater than what had been observed in bovine milk at much higher latitude. Taking into account all the aforementioned information, we hypothesized that seasonal changes in the chemical composition of camel milk may reflect an endogenous circannual biological rhythm with a strong underlying pacemaker that is generated by the circadian system and entrained by environmental cues (Casey and Plaut, 2012;Suárez-Trujillo and Casey, 2016). To support this hypothesis, El Allali et al (2013) recently demonstrated the existence of an endogenous circadian clock in dromedaries by describing rhythmic daily changes in body temperature under a constant photoperiod and ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…To support this hypothesis, El Allali et al (2013) recently demonstrated the existence of an endogenous circadian clock in dromedaries by describing rhythmic daily changes in body temperature under a constant photoperiod and ambient temperature. In addition, an increasing body of evidence suggests that central and peripheral (mammary gland) circadian clocks regulate both the daily and seasonal changes in expression of genes in the mammary gland that are responsible for controlling milk synthesis (Casey and Plaut, 2012;Suárez-Trujillo and Casey, 2016). The positive effect of photoperiod on milk yield has already been demonstrated in several dairy animal species (Dahl et al, 2012), but in vivo data associating circannual changes in milk composition with endogenous rhythms or photoperiod are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Other likely actions not covered here include mammary gland development 65 , allergic airway inflammation 66 , and intercellular signaling in taste buds 67 . The appreciation of these contributions of 5-HT to an assortment of body functions offers opportunities to gain a better understanding of the mechanisms involved in their regulations, and it also draws attention to systems that could be inadvertently affected by therapies that target elements of 5-HT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal changes to sensitize the maternal brain to mothering involve several complex systems. We have earlier discussed the oxytocinergic and the dopaminergic systems, but there are also endorphin systems, prolactin and mammary physiology, serotonin systems (Suarez-Trujillo & Casey, 2016), and epinephrine and stress-related systems (Buckley, 2015). Animal parenting has been extensively studied (Kinsley & Lambert, 2008), allowing also a life history interpretation of what is involved for the human mother and family.…”
Section: Maternal Neurobehavior and Sensitizationmentioning
confidence: 99%